Verifikasi Penentuan Kadar Sitronelal dalam Minyak Sereh Wangi Menggunakan GCFID - Surani Surani; Renardi Erwinsyah (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Citronella oil is one of the essential oils, where the main component is Citronellal. The Instrumental Chemistry Laboratory is a testing laboratory that accepts citronella oil testing samples from both Chemistry Study Program students at the Indonesian University of Education and external students. As a testing laboratory, the analysis must use proven methods, procedures, and equipment to ensure the suitability and purpose of the test. Currently, the Instrumental Chemistry Laboratory will propose and implement ISO/IEC 17025 so that the test results are more valid, consistent, and accountable. The purpose of this study was to verify the method for determining citronellal levels in citronella oil using GC-FID, where the samples used were samples from the isolation and synthesis of organic compounds practicum by chemistry study program students. The results of the study for the linearity of the citronellal standard obtained a correlation value of 0.9988 and has entered the linearity quality requirement of 0.9950. From the results of the accuracy test measurements, the recovery value was 91.15% and entered the quality requirement of 80-110%. From the results of the precision test measurements, the RSD value was 1.87%, which was within the quality requirements of <2%. The limit of detection and limit of quantitation were determined with LOD results of 2.72% and LOQ of 9.06%. Based on the results of the verification study, the method for analyzing citronellal levels in citronella oil using GC-FID has met the acceptance requirements, so it can be concluded that this method has been verified